Pre-recorded power statement usage on collegiate male hockey athletes - Leaf, B.; Youll, L.; Murray, S. (Journal of Athletic Enhancement, 2017)
Athletes during sport performance encounter stress levels which affect performance outcome. Pre-performance rituals and/or practices vary amongst individual athletes and assist the athlete with their ability to focus during performance. Athletes attain the ability to control distractions through exercises of mental preparation such as guided imagery, observation of performance, and sport-specific power statements. The athletes involved in the current study were members of a team which is a competitive performance club league in the American Collegiate Hockey Association (ACHA). A recording consisting of 40 hockey specific power statements was randomly assigned to 10 members of the team by an independent source and the other 10 members received a recording asking the athlete to continue on their normal pre-practice routine. The athletes were advised to listen to the recording directly before the practice and then were observed. Data was collected on the pass completion/ incompletion and goal completion/incompletion pre-treatment on a separate occasion and data collection was repeated after treatment was applied. It was predicted that the completion of goals and passes would increase in those athletes receiving treatment and the results in the athletes not treated would remain the same as in the pre-treated results. Results of the data collected show a significant relationship to the intended result in passing completion and a positive trend in goal completion in the athletes who received the treatment. Results of the athletes not receiving treatment were the same as the intended result, an acute deviation from pre-treatment statistics.